Trophic ecology of the Eurasian otter (Lutra lutra) - Drake, Lorna (2020)
Generalist apex predators have broad diets, consuming species from a range of trophic levels and connecting multiple energetic pathways. Investigating the diet of generalist apex predators thus provides a unique opportunity to describe trophic interactions over space and time, and can be used to gain an insight into ecosystem level changes. Broad spatio-temporal and demographic variation in the diet of the Eurasian otter (Lutra lutra), an apex predator of freshwater ecosystems, were investigated using a biobank of tissue samples and data collected from dead otters in England and Wales over 23 years. Molecular methods were utilised to gain a greater insight into otter diet, with stable isotope analysis revealing broad-scale variation in nutrient assimilation, and DNA metabarcoding provided a more precise description of the species consumed by otters. Isotopic signatures suggested nutrient assimilation by otters was driven by changes in basal nutrient levels and prey availability. Variation in nitrogen isotopes may reflect landscape scale differences in anthropogenic inputs from fertilisers, which were suggested to enrich basal nitrogen signatures within the environment and thus enrich signals throughout the trophic network, with some additional changes driven by differences in the consumption of high trophic level prey by otters. Variation in carbon isotopes of otters reflected changes in the availability of marine-derived nutrients, with otters sampling such nutrients primarily via consumption of marine prey at the coast and anadromous fish inland. Analysis of DNA metabarcoding data revealed otters consumed a broad range of prey from a variety of habitats. Stocked fish, invasive species and protected species occurred in the diet of otters infrequently, with the exception of the critically endangered European eel (Anguilla anguilla), which was one of the most frequently consumed prey items. Dietary variation primarily reflected seasonal changes in prey availability and differences in prey distributions across the ...